2012
DOI: 10.3758/s13423-012-0219-9
|View full text |Cite
|
Sign up to set email alerts
|

Working memory can enhance unconscious visual perception

Abstract: We demonstrate that unconscious processing of a stimulus property can be enhanced when there is a match between the contents of working memory and the stimulus presented in the visual field. Participants first held a cue (a colored circle) in working memory and then searched for a brief masked target shape presented simultaneously with a distractor shape. When participants reported having no awareness of the target shape at all, search performance was more accurate in the valid condition, where the target matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…This pattern of results suggests that merely priming an object's representation did not influence spatial resolution, although the object was perceptually identified. This is in line with the findings of previous studies that showed null effects of perceptual priming from a visual cue on visual search when the cue is irrelevant to the search task (e.g., Pan, Cheng, & Luo, 2012;Soto, et al, 2005;2010). We also compared accuracy on the spatial resolution task between Experiments 2 and 3, which yielded a significant interaction effect, F(1, 38) = 6.112, p = .018, partial η 2 = .139.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…This pattern of results suggests that merely priming an object's representation did not influence spatial resolution, although the object was perceptually identified. This is in line with the findings of previous studies that showed null effects of perceptual priming from a visual cue on visual search when the cue is irrelevant to the search task (e.g., Pan, Cheng, & Luo, 2012;Soto, et al, 2005;2010). We also compared accuracy on the spatial resolution task between Experiments 2 and 3, which yielded a significant interaction effect, F(1, 38) = 6.112, p = .018, partial η 2 = .139.…”
Section: Resultssupporting
confidence: 78%
“…Previous research has shown that working memory-driven attention can improve identification accuracy or sensitivity to a target when it appears at the location of the memorymatching item in the visual field (Han, 2015b;Pan, Cheng, & Luo, 2012;Soto, et al, 2010). However, because the reported attentional effect occurred only under the condition where the target was always presented with distractors and followed by masks, it might be due to the mechanisms of spatial uncertainty reduction and/or external noise exclusion (Cosman & Vecera, 2011;Dosher & Lu, 2000a, 2000bShiu & Pashler, 1994).…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…Previous studies of visual awareness have tended to use coarse measures of awareness, such as forced-choice judgments of shape or pattern (e.g., Olivers, Meijer, & Theeuwes, 2006;Pan, Cheng, & Luo, 2012). That is, most studies of visual perception have tended to focus on the question of sensitivity.…”
mentioning
confidence: 99%